We need to complete the square of the next two equations:
![\begin{gathered} x^2-4x \\ \text{and} \\ y^2-6y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1oidzd0d3ggbb8j8qldjwk7vjtdieyujm3.png)
We know that:
![(x-2)^2=x^2+2\cdot x\cdot(-2)+(-2)^2=x^2-4x+4](https://img.qammunity.org/2023/formulas/mathematics/college/j7m1dz9r5ib3zc5x2tvpzl2x0171zwhhjf.png)
and:
![(y-3)^2=y^2+2\cdot y\cdot(-3)+(-3)^2=y^2-6y+9](https://img.qammunity.org/2023/formulas/mathematics/college/fqpp6upr57fptdsj1zyk2i8m8k2k115f9q.png)
Adding and subtracting 4 and 9 to the original equation, we get:
![\begin{gathered} x^2+y^2-4x-6y+8=0 \\ x^2+y^2-4x-6y+8+4-4+9-9=0 \\ (x^2-4x+4)+(y^2-6y+9)+(8-4-9)=0 \\ (x-2)^2+(y-3)^2-5=0 \\ (x-2)^2+(y-3)^2=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jvibtwci1tqixfkhyxhh9f9ahl80xx7itw.png)
This equation has the next form:
![(x-h)^2+(y-k)^2=r^2](https://img.qammunity.org/2023/formulas/mathematics/college/5s77z5lwu6jnvb5vkwanu2jvhq5sh1qkc3.png)
which corresponds to a circle centered at (h,k) with radius r. Then, in our equation, the center is (2,3) and the radius is √5.